KEWENANGAN DEKONSENTRASI DALAM PENYELENGGARAAN OTONOMI DAERAH DAN PERMASALAHAN PENYELENGGARAANYA* DI DAERAH - PKP2A III LAN, Tim (Jurnal Borneo Administrator, 2008)
Governance management framework in autonomy framework relies on 3 especial principal, decentralization, dekonsentrasi anda medebewind (Tugas Pembantuan). In the united state corridor, dekonsentrasi and decentralization dekonsentrasi and decentralization cannot be dichotomized, both have to fill and strengthen each other. Dekonsentrasi is often said have strategic function to unify the Republic of Indonesia. Unfortunately, the regulation of dekonsentrasi management is still the minimum grade. This condition has been appropriately generating many problems so that central government have to give serious attention through releasing regulation or policy in synergizing function, institution and programs in dekonsentrasi management so that it can walk as its goals.   Key words : Desentralisasi, Dekonsentrasi